A STUDY OF THE HISTORICAL CAPITAL OF POLITICAL EDUCATION ON THE INDEPENDENCE MOVEMENT IN INDONESIA - Hermawan , Iyep Candra (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to analyze the historical capital of political education as the nation's capital in the struggle for independence in Indonesia. The method used in this article is qualitative research with a historical approach. The conclusion of this article is a historical event that is very important and significantly influences the formation of the attitude of Indonesian nationalism towards Indonesian independence. The historical roots of Indonesian nationalism began at the beginning of the 20th century with the formation of a national movement container known as the Budi Utomo 1908. The unity of the organization embodied in Budi Utomo became a battering era that had influenced and strengthened the nation's generation which was later manifested in the 1928 Youth Oath declaration. The value of national unity and unity is bound in the statement of the Youth Pledge as a solidity and firmness of the nation, namely “the nation, language and homeland of Indonesia”. A multicultural and multi-ethnic nation generation unites in the Youth Pledge and fights for Indonesian independence. The culmination point of the nation's struggle with a solid and integrated attitude of nationalism carved out the nation's generation and incarnated in the era of Indonesia's independence which was proclaimed on August 17, 1945 and made the Indonesian state an independent, united and sovereign nation. National Awakening, Youth Oaths, and Proclamation of Independence as historical capital for the nation's political education in the Indonesian independence movement.